MODEL MATEMATIKA DALAM MENENTUKAN POPULASI POHON DI KAMPUS II UIN ALAUDDIN MAKASSAR SEBAGAI CARBON SINKS - Ermawti, Ermawati; Muslini, Erly (Jurusan Matematika FST-UIN Alauddi Makassar, 2014)
There is air pollution who made by vehicle everyday can reduce healthy air quality if vailable trees is not enough to absorb pollution air gasses. This research to form pollution rate and air cleaning rate or carbon sinks into differential equation system and explain solution of mathematics model into minimal amount of trees who must be added to minimize pollution rate five years later. This research is observation and immediately going to research place calculate amount of tree and vehicle.